Ttfn - Myracle, Lauren, 1969- (New York : Amulet Books, 2006)
Now high school juniors, Zoe, Maddie, and Angela continue to share "instant messages" with one another as one of them experiments with marijuana, another gets her first boyfriend, and the third moves three thousand miles away.
Sequel to: Ttyl.
Keywords: Instant messaging -- Fiction; Friendship -- Fiction; Moving, Household -- Fiction; Marijuana -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction